30-year nationwide trends in incidence of atrial fibrillation in Denmark and associated 5-year risk of heart failure, stroke, and death. (15th December 2016) - Schmidt, Morten; Ulrichsen, Sinna Pilgaard; Pedersen, Lars; Bøtker, Hans Erik; Nielsen, Jens Cosedis; Sørensen, Henrik Toft
Abstract: Background: Long-term nationwide trends in atrial fibrillation (AF) incidence and 5-year outcomes are rare. Methods: We conducted a population-based cohort study using the Danish National Patient Registry covering all Danish hospitals. We computed standardized incidence rates during 1983–2012. We used Cox regression to estimate hazard ratios (HRs) of heart failure, stroke, and death within 5 years, comparing 5-year calendar periods with the earliest period (1983–1987) as reference. Results: We identified 312, 420 patients with first-time hospital-diagnosed AF. The incidence rate per 100, 000 person-years increased from 98 in 1983 to 307 in 2012. The mean annual increase during the 30-year study period was 4%, with a 6% increase annually until 2000 and a 1.4% increase annually thereafter. The incidence trends were most pronounced among men and persons above 70 years. Among high-risk subgroups, AF incidence was consistently highest in patients with valvular heart disease or heart failure. The rate of heart failure following AF declined by 50% over the entire study period (HR: 0.49, 95% confidence interval (CI): 0.48–0.51) and the mortality rate declined by 40% (HR: 0.62, 95% CI: 0.61–0.63). Within the last two decades, the rate for ischemic stroke declined by 20% (HR 0.81, 95% CI: 0.78–0.84), but increased almost as much for haemorrhagic stroke (HR: 1.14, 95% CI: 1.01–1.29). Conclusions: The long-term risk of heart failure, ischemic stroke, and death following onset of AF has decreased remarkably over the last three decades. Still, the threefold increased incidence of hospital-diagnosed AF during the same period is a major public health concern.